2006
DOI: 10.1097/01.sap.0000226944.08332.41
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Technique for Microsurgically Unreplantable Fingertip Amputations

Abstract: Reattachment of the amputated fingertips as composite grafts has been performed for distal levels in children, with high rates of good outcome, but the majority of the reports emphasized that this procedure had success rates only up to 50% in adults. Several techniques to enhance composite graft take in adults have been defined. In this study, a technique to enhance nonmicrosurgical replantation of amputated fingertips as composite grafts is presented.Twenty-three patients were treated with this technique, 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Table 2 provides a comparison between our results and those reported in the literature. [3][4][5]31,32 The success rate of our series was satisfactory, and the objective 2-point discrimination was acceptable. The esthetic result evaluated by the patients' self-report indicated that nearly all patients (93.5%) were satisfied and two patients had complications.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Table 2 provides a comparison between our results and those reported in the literature. [3][4][5]31,32 The success rate of our series was satisfactory, and the objective 2-point discrimination was acceptable. The esthetic result evaluated by the patients' self-report indicated that nearly all patients (93.5%) were satisfied and two patients had complications.…”
Section: Discussionmentioning
confidence: 74%
“…The common situations that prevent the microsurgical replantation of a fingertip amputation include the lack of appropriate vessels to reanastomose because of the distal level of the amputation, severe soft tissue crush injury, high risk of prolonged surgery in older people, unavailability of microscopic equipment, and loss of the distal amputated fingertip. 4,7,8 Distal pulp injury classified as Allen's type I can be treated conservatively and will heal by secondary intention. 1 The wound can be covered with a nonadherent dressing and will heal by scar contraction and epithelialization in 3 weeks to 6 weeks, depending on the size of the defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a consensus that replantation is the best choice by maintaining the length of the finger and the normal anatomy of the nail complex, if only the amputated fragment is available, in replantable condition and well preserved [34,42]. If replantation is not possible, reconstruction ladder could be used for fingertip injuries: secondary healing, primary closure, skin grafting, homodigital flaps (V-Y advancement [4], V-Y cup [41], dorsal visor [20], Kutler [25], Moberg [35], hatchet [4], Hueston [10], linguiform rotation [12], dorsal adipofascial flaps [26,28,40], cross-finger flap [20,25], island flaps (homodigital [5,7,13,29,38], heterodigital [30] and metacarpal [19]) (antegrade and retrograde [38]), digital artery perforator flaps [23], distant flaps (thenar flap [10], groin and abdominal), free flap (free toe pulp [9,22,31], venous [33,39] and medial plantar perforator [17,42]). …”
Section: Discussionmentioning
confidence: 99%
“…Treatment of fingertip injuries ranges in a large spectrum which correlates to the reconstruction ladder: secondary intention, primary closure, grafting (split, full thickness and composite [35,41]) and flaps. Flaps are classified mainly into homodigital flaps [4,10,12,17,20,25,33,39,42], heterodigital flaps (cross-finger flap [7,29]), distant flaps [10], island flaps (homodigital [1,5,13,38,44], heterodigital [30] and metacarpal [19]), perforator flaps [23] and free flaps [9,21,24,27,45].…”
Section: Introductionmentioning
confidence: 99%